The comprehensive analysis of DEG/ENaC subunits in Hydra reveals a large variety of peptide-gated channels, potentially involved in neuromuscular transmission - Assmann, Marc Christopher; Kuhn, Anne; Holstein, Thomas W. (BMC biology, 2014)
It is generally the case that fast transmission at neural synapses is mediated by small molecule neurotransmitters. The simple nervous system of the cnidarian Hydra, however, contains a large repertoire of neuropeptides and it has been suggested that neuropeptides are the principal transmitters of Hydra. An ion channel directly gated by Hydra-RFamide neuropeptides has indeed been identified in Hydra - the Hydra Na+ channel (HyNaC) 2/3/5, which is expressed at the oral side of the tentacle base. Hydra-RFamides are more widely expressed, however, being found in neurons of the head and peduncle region. Here, we explore whether further peptide-gated HyNaCs exist, where in the animal they are expressed, and whether they are all gated by Hydra-RFamides. We report molecular cloning of seven new HyNaC subunits - HyNaC6 to HyNaC12, all of which are members of the DEG/ENaC gene family. In Xenopus oocytes, these subunits assemble together with the four already known subunits into thirteen different ion channels that are directly gated by Hydra-RFamide neuropeptides with high affinity (up to 40 nM). In situ hybridization suggests that HyNaCs are expressed in epitheliomuscular cells at the oral and the aboral side of the tentacle base and at the peduncle. Moreover, diminazene, an inhibitor of HyNaCs, delayed tentacle movement in live Hydra. Our results show that Hydra has a large variety of peptide-gated ion channels that are activated by a restricted number of related neuropeptides. The existence and expression pattern of these channels, and behavioral effects induced by channel blockers, suggests that Hydra co-opted neuropeptides for fast neuromuscular transmission.
Gesehen am 14.02.2017